High-yielding and quality banana production through plant growth-promoting rhizobacterial (PGPR) inoculation - Mia, Md. Abdul Baset; Shamsuddin, Zulkifli; Wahab, Zakaria; Mahmood, Marziah (2005)
Introduction. Rhizobacterial inoculation in low fertilizer-N conditions, viz., 33% fertilizer-N of the total N requirement, could produce similar plant growth to the 100% N-fertilization of banana plantlets grown under hydroponic conditions. Thus, we tested PGPR inoculation in combination with fertilizer-N application to study the role played by strains of rhizobacteria in nutrient accumulation, nitrogen fixation and, consequently, improvement in yield and fruit quality of bananas. Materials and methods. Two PGPR strains were used in the experiments, namely, Sp7 (Azospirillum brasilense) and UPMB 10 (Bacillus sphaericus). The design of the experiment was completely randomized with three replications. Eight treatments were applied: control without fertilizer-N application (N0%) and without PGPR; N 0% + Sp7; N0% + UPMB10; N 33% without PGPR; N33% + Sp7; N33% + UPMB10; N100% without PGPR and N100% + UPMB10. One tissue-cultured banana (cv. 'Berangan') plantlet was planted in a plastic pot (4 L) for 45 days and thereafter transferred to a larger polyethylene tank (1000 L) until maturity. A 100-mL broth culture of Sp7 or UPMB10 was added to the respective tanks after the transplanting process and repeat inoculations were performed monthly. The fruits were harvested at the maturity stage after 80-90 days of flowering. After ripening, yield and fruit quality parameters were assessed. Results. Inoculation with 33% fertilizer-N increased the total nutrient accumulation (N, P, K, Ca and Mg). PGPR inoculation along with 33% fertilizer-N significantly increased the bunch yield and fruit physical attributes, namely, finger weight, length and diameter, and [pulp / peel] ratio, besides inducing early flowering by 3 weeks. Conclusion. The results suggested that PGPR strains Sp and UPMB10 could be used as bioenhancer and biofertilizer for early, high-yielding and improved banana fruit production in 33% fertilizer-N conditions. © 2005 Cirad/EDP Sciences. All rights reserved